1997
DOI: 10.1111/j.1600-0773.1997.tb01964.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tolerability Profile of Novel, Potent Bisphosphonates in Two Short‐Term Rat Models

Abstract: Abstract:Bisphosphonates are used clinically to inhibit bone resorption but they may also cause renal damage. For the profiling of new, potent bisphosphonates, their adverse renal effects were investigated in 2 rat models. In the first model, bisphosphonate was repeatedly injected (1 mg/kg, subcutaneously) over 2 weeks and the urinary excretion of malate dehydrogenase was monitored to assess nephrotoxic potential. Of the 6 new compounds tested, 3 markedly elevated malate dehydrogenase whereas 3 others caused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…Similarly, a previous study with a single dose of intravenous ibandronate and zoledronate (1 mg/kg, and 1 or 3 mg/kg, respectively) in 34-week old rats showed that 4 days after dosing there was no significant change in the majority of biochemical parameters and urinary enzymes compared with controls (Pfister et al 2003). Conversely, immediate changes in renal function have been reported for pamidronate and zoledronate in an acute renal tolerability model in the rat (Cal & Daley-Yates 1990;Green et al 1997). However, considering the delayed onset of structural changes with all three bisphosphonates in our studies, it is likely that these early effects are due to functional changes rather than to acute tubular injury.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a previous study with a single dose of intravenous ibandronate and zoledronate (1 mg/kg, and 1 or 3 mg/kg, respectively) in 34-week old rats showed that 4 days after dosing there was no significant change in the majority of biochemical parameters and urinary enzymes compared with controls (Pfister et al 2003). Conversely, immediate changes in renal function have been reported for pamidronate and zoledronate in an acute renal tolerability model in the rat (Cal & Daley-Yates 1990;Green et al 1997). However, considering the delayed onset of structural changes with all three bisphosphonates in our studies, it is likely that these early effects are due to functional changes rather than to acute tubular injury.…”
Section: Discussionmentioning
confidence: 98%
“…Monthly oral administration of 50 mg of minodronate has much more efficacy in terms of the incidence of vertebral fractures (2.2% in a group receiving oral administration of 1 mg of minodronate daily vs. 0.9% in a group receiving oral administration of 50 mg once per month) (8). The dosedependent nephrotoxicity of bisphosphonate has been reported in animal models (15). Since the oral administration of high-dose (56 mg) minodronate produces more than 20-fold higher maximum plasma concentrations than the oral administration of 1 mg of minodronate (based on the package insert of Bonoteo), it is possible that such a high plasma minodronate concentration can induce renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have demonstrated that zoledronic acid is a potent inhibitor of bone resorption and has a favorable tolerability profile [58,59,66,69]. The available clinical data have demonstrated that zoledronic acid is safe and highly effective in normalizing serum calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some bisphosphonates have been associated with impairment of renal function in humans [40,65], zoledronic acid has exhibited a mild renal toxicity profile [66].…”
Section: Pivotal Trialsmentioning
confidence: 99%